Preparation, characterization and application of Ni catalyst for hydrogen production by thermocatalytic decomposition of methane - Balasubramanian, Subramaniam (2017)
The purpose of this work was to prepare and characterize a simple and stable nickel catalyst for the thermocatalytic decomposition (TCD) of methane to hydrogen. The nickel catalyst was prepared by the method of electroless plating whereby metallic nickel particles aggregates with controlled crystalline size and primary particle size on a glass wool fibre support. This was followed by the application of the catalyst for the TCD reaction of methane gas to hydrogen gas in an oxygen-free atmosphere. XRD, EDX and FESEM results had proved that the 40 minutes of nickel precipitation time showed excellent nickel precipitation compared to the 20 minutes precipitation time sample. The catalyst was then characterized. From the temperature programmed reduction, the optimal temperature for reduction was between 473K and 513K and the most optimal precipitation time for nickel was between 30 to 40 minutes. The field emission scanning electron microscope images showed good precipitation of nickel (precipitation time of 40 minutes) on the glass support however the images of the catalyst after the TCD process showed significant amount of sintering had occurred. Energy dispersive x-ray results also showed an increase in carbon on the surface with an absence of palladium and tin. This suggests that nickel had coalesced and encapsulated by carbon aggregation. Gas chromatograph results showed less than 10% conversion rates of methane and this proved that deactivation of the catalyst had occurred in the early stages due to sintering and carbon encapsulation. This poor result could be attributed to the poor precipitation of nickel on the 20 minutes catalyst sample that was used for the conversion and also due to the sintering of catalyst in the early stages of the experiment.